Preparation method of lithium-sulfur battery diaphragm

By using materials such as polyimide and boron nitride, combined with plasma treatment and ultrasonic dispersion, lithium-sulfur battery separators with high mechanical strength and thermal stability were prepared, which solved the problem of insufficient mechanical strength and thermal stability of lithium-sulfur battery and improved the cycle stability and rate performance of the battery.

CN119542674AInactive Publication Date: 2025-02-28QINGDAO UNIV OF SCI & TECH

Patent Information

Application Number
CN202411725907.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In practical applications of lithium sulfur batteries, the insulation of the active substance sulfur and its discharge product polysulfide, the capacity attenuation caused by the dissolution and migration of polysulfides, and the volume changes during the charge and discharge process, making the mechanical strength and thermal stability of lithium sulfur batteries poor.

Method used

Polyimide is used as the base material and boron nitride is used as two-dimensional material to prepare lithium-sulfur battery separators through plasma treatment, ultrasonic dispersion and impregnation lifting methods to improve their mechanical strength and thermal stability.

Benefits of technology

It significantly improves the mechanical strength and thermal stability of the lithium-sulfur battery separator, reduces the risk of volume changes during capacity attenuation and charging and discharge, and improves the cycle stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur battery materials, and discloses a lithium-sulfur battery diaphragm preparation method, which comprises: 1, material preparation: using polyimide as a base material, boron nitride as a two-dimensional material, and deionized water as a solvent; step 2, substrate material pretreatment: placing a substrate film on a sample table of plasma treatment equipment, closing the equipment, vacuumizing to a set pressure, starting plasma treatment, setting power and time, taking out the film after the treatment is completed, and naturally airing; step 3, preparing dispersion liquid, namely weighing 0.5 g of boron nitride powder; according to the preparation method of the lithium-sulfur battery diaphragm, polyimide is selected as a base material and has excellent mechanical strength, thermal stability, chemical stability and electrical insulation performance, and the base material is chemically modified and physically treated in the preparation process; therefore, the effect of improving the mechanical strength and the thermal stability of the lithium-sulfur battery diaphragm can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium-sulfur battery materials, and in particular to a method for preparing a lithium-sulfur battery separator. Background Art

[0002] Lithium-sulfur battery separator is an important component of lithium-sulfur battery. It is mainly used to physically isolate the positive and negative electrodes of the battery. Its main function is to allow lithium ions to pass freely during the charging and discharging process, while preventing direct contact between the positive and negative electrodes of the battery, thereby ensuring the safety and stability of the battery. The performance of the separator has a crucial impact on the working efficiency, cycle life, energy density and safety of lithium-sulfur batteries.

[0003] With the development of new energy technologies, the demand for high-performance energy storage systems is growing. Lithium-sulfur batteries have attracted widespread attention due to their high theoretical energy density, low cost and environmental friendliness. However, in practical applications, the mechanical strength and thermal stability of lithium-sulfur batteries are poor due to the insulating properties of the active substance sulfur and its discharge product polysulfide, the capacity decay caused by the dissolution and migration of polysulfides (i.e., the shuttle effect), and the large volume change during charging and discharging. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a lithium-sulfur battery separator, which has the advantages of improving the mechanical strength and thermal stability of the lithium-sulfur battery separator, and solves the problems of the above-mentioned technology.

[0006] Technical Solution

[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a lithium-sulfur battery separator, comprising the following steps:

[0008] Step 1: Material preparation, using polyimide as the substrate, boron nitride as the two-dimensional material, and deionized water as the solvent;

[0009] Step 2: Pretreatment of the substrate material: Place the substrate film on the sample stage of the plasma treatment equipment, close the equipment, evacuate to the set pressure, start the plasma treatment, set the power and time, and after the treatment is completed, take out the film and dry it naturally;

[0010] Step 3: Preparation of dispersion: weigh 0.5g of boron nitride powder, add 0.1g of PVA to 100ml of deionized water, heat to 80°C and stir until completely dissolved to form a dispersant solution, add 0.5g of boron nitride powder to 100ml of dispersant solution, use an ultrasonic cleaner to ultrasonically disperse at 40°C for 2 hours to ensure that the boron nitride is evenly dispersed to form a stable boron nitride dispersion;

[0011] Step 4: Preparation of the coating layer: using the immersion and pulling method, slowly immerse the pretreated polyimide film into the two-dimensional material dispersion, stay for 30 seconds, then pull it out of the liquid surface at a constant speed (1 mm / s), dry it naturally for 12 hours, repeat the above immersion and pulling process 2-3 times, and then carry out the next coating after each drying;

[0012] Step 5: Curing treatment: put the coated film into an oven and heat it at 120°C for 1 hour to firmly fix the coating on the substrate, and then cool it naturally to room temperature to complete the preparation of the diaphragm;

[0013] Step 6: Test optimization. Use a scanning electron microscope (SEM) to observe the surface morphology and coating uniformity of the diaphragm, measure the porosity through a porosimeter, and evaluate the wettability of the electrolyte using a contact angle meter. Apply the prepared diaphragm to lithium-sulfur batteries to test its cycle stability, rate performance, capacity retention and other indicators. According to the test results, adjust the dispersion content, coating times and other parameters to obtain the best diaphragm performance.

[0014] The substrate material pretreatment includes chemical modification and physical treatment. The chemical modification uses a modifier containing an amino group or a carboxyl group. The modifier (such as γ-aminopropyltriethoxysilane) is dissolved in an appropriate amount of solvent (such as ethanol) to prepare a solution with a concentration of 1%. The substrate film is immersed in the modifier solution to ensure that the film is completely immersed. The film is immersed at room temperature for 30 minutes, the film is taken out, rinsed with deionized water, excess modifier is removed, and the film is placed in an oven and dried at 80°C for 1 hour to firmly fix the modifier on the substrate surface.

[0015] The physical treatment uses a laser etching device, placing the substrate film on the workbench of the laser etching device, setting appropriate laser power and scanning speed, performing laser etching to form a uniform microstructure, cleaning with deionized water to remove the residues produced by etching, and placing the film in an oven to dry at 80°C for 1 hour.

[0016] The concentration of the dispersant is generally between 0.1% and 1%, and the dispersion time is ensured to be long enough, usually 1 to 2 hours, to completely break up the agglomeration of the nanomaterials.

[0017] During the ultrasonic dispersion, the temperature is controlled at about 40° C. to improve the dispersion effect. Too high a temperature may cause solvent evaporation or thermal decomposition of the nanomaterial. A thermometer is used to monitor the temperature of the dispersion to ensure that it remains within a suitable range.

[0018] A method for preparing a lithium-sulfur battery separator comprises the following steps:

[0019] Ⅰ: Select materials;

[0020] II: Preparation of membrane materials;

[0021] III: functionalized diaphragm surface;

[0022] IV: Drying and heat treatment;

[0023] V: Testing and evaluation.

[0024] Compared with the prior art, the present invention provides a method for preparing a lithium-sulfur battery separator, which has the following beneficial effects:

[0025] The preparation method of the lithium-sulfur battery separator uses polyimide as a substrate, which has excellent mechanical strength, thermal stability, chemical stability and electrical insulation performance, and chemically modifies and physically treats the substrate material during the preparation process, thereby achieving the effect of improving the mechanical strength and thermal stability of the lithium-sulfur battery separator. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Embodiment 1

[0028] A method for preparing a lithium-sulfur battery separator comprises the following steps:

[0029] Step 1: Material preparation, using polyimide as the substrate, boron nitride as the two-dimensional material, and deionized water as the solvent. Polyimide, as a high-performance engineering plastic, has excellent mechanical strength, thermal stability, chemical stability and electrical insulation properties. Boron nitride, as a two-dimensional material, has a high specific surface area, excellent thermal conductivity and chemical stability. The high mechanical strength and rigidity of boron nitride can significantly enhance the mechanical properties of the polyimide substrate, making it more stable during the charge and discharge process and reducing the risk of deformation and rupture. The interfacial interaction between boron nitride and polyimide (such as van der Waals force and hydrogen bond) can further improve the mechanical strength of the composite material. The thermal decomposition temperature of boron nitride is much higher than that of polyimide, which can provide additional protection at high temperatures to prevent the thermal decomposition of polyimide. Boron nitride has good chemical stability and inertness, which can improve the compatibility of the diaphragm with the electrolyte and reduce the occurrence of side reactions. Boron nitride has a high specific surface area and good adsorption capacity, which can effectively adsorb polysulfides and reduce their shuttling between the positive and negative electrodes;

[0030] Step 2: Pretreatment of the substrate material: Place the substrate film on the sample stage of the plasma treatment equipment, close the equipment, evacuate to the set pressure, start the plasma treatment, set the power and time, and after the treatment is completed, take out the film and dry it naturally;

[0031] Step 3: Preparation of dispersion: weigh 0.5g of boron nitride powder, add 0.1g of PVA to 100ml of deionized water, heat to 80°C and stir until completely dissolved to form a dispersant solution, add 0.5g of boron nitride powder to 100ml of dispersant solution, use an ultrasonic cleaner to ultrasonically disperse at 40°C for 2 hours to ensure that the boron nitride is evenly dispersed to form a stable boron nitride dispersion. The dispersant can reduce the surface tension of the boron nitride particles, prevent the particles from agglomerating, ensure that the boron nitride is evenly dispersed in the solvent, and form a protective layer on the surface of the boron nitride particles to prevent the particles from settling or reagglomerating during long-term storage. The evenly dispersed boron nitride particles can ensure that the coating is evenly distributed on the surface of the substrate, avoiding performance differences caused by uneven coating. The uniform coating can improve the mechanical strength and thermal stability of the diaphragm and reduce defects and holes.

[0032] Step 4: Preparation of the coating layer: using the immersion pulling method, slowly immerse the pretreated polyimide film into the two-dimensional material dispersion, stay for 30 seconds, then pull it out of the liquid surface at a constant speed (1mm / s), dry it naturally for 12 hours, repeat the above immersion pulling process 2-3 times, and then coat it again after each drying. The functional coating can significantly improve the mechanical strength of the diaphragm, making it less likely to break during the charge and discharge process, improve the toughness of the diaphragm, and reduce damage caused by external stress. The immersion pulling method can ensure that the coating is evenly distributed on the surface of the substrate, avoiding performance differences caused by uneven coating;

[0033] Step 5: Curing treatment: put the coated film into an oven and heat it at 120°C for 1 hour to firmly fix the coating on the substrate. Cool it naturally to room temperature to complete the preparation of the diaphragm. Heat treatment can physically cross-link the polymer chains in the coating to form a stable network structure, improve the mechanical strength of the coating, remove the solvent in the coating, make the coating material more compact, improve the thermal stability of the coating, make the coating material better penetrate into the micropores on the surface of the substrate, enhance the adhesion between the coating and the substrate, make the solvent in the coating evaporate evenly, avoid bubbles and cracks in the coating, and improve the uniformity and density of the coating;

[0034] Step 6: Test optimization. Use a scanning electron microscope (SEM) to observe the surface morphology and uniformity of the membrane. The uniformity and surface morphology of the coating can be observed intuitively, and possible defects or uneven areas can be found. The porosity is measured by a porosimeter. The porosity directly affects the penetration of the electrolyte and the transmission efficiency of lithium ions. The test can optimize the porosity and improve the battery performance. The contact angle meter is used to evaluate the wettability of the electrolyte. The smaller the contact angle, the better the wettability of the electrolyte, the higher the lithium ion transmission efficiency, and the better the battery performance. The prepared membrane is applied to lithium-sulfur batteries to test its cycle stability, rate performance, capacity retention rate and other indicators. The cycle stability test can be used to evaluate the performance of the membrane in actual use. Energy stability, discover potential problems and optimize them, evaluate the performance of the diaphragm under high-rate charge and discharge conditions, optimize the conductivity and ion transport properties of the diaphragm, adjust the dispersion content, coating times and other parameters according to the test results, in order to obtain the best diaphragm performance, find the optimal boron nitride content to balance the mechanical strength, thermal stability and electrochemical properties of the diaphragm, select the most suitable dispersant and concentration to ensure the stability of boron nitride in the dispersion and the uniformity of the coating, find the best dispersion time to ensure the uniform dispersion of boron nitride, avoid material damage caused by excessive ultrasound, select the most suitable coating method to ensure the uniformity of the coating and the consistency of thickness, find the best curing conditions to ensure the firmness and stability of the coating.

[0035] The pretreatment of the substrate material includes chemical modification and physical treatment. The chemical modification uses a modifier containing an amino group or a carboxyl group. The modifier (such as γ-aminopropyltriethoxysilane) is dissolved in an appropriate amount of solvent (such as ethanol) to prepare a solution with a concentration of 1%. The substrate film is immersed in the modifier solution to ensure that the film is completely immersed. The film is immersed at room temperature for 30 minutes, the film is taken out, and it is rinsed with deionized water to remove excess modifier. The film is placed in an oven and dried at 80°C for 1 hour to firmly fix the modifier on the substrate surface.

[0036] Physical treatment uses laser etching equipment. The substrate film is placed on the workbench of the laser etching equipment. Appropriate laser power and scanning speed are set to perform laser etching to form a uniform microstructure. The film is cleaned with deionized water to remove the residue produced by etching. The film is placed in an oven and dried at 80°C for 1 hour.

[0037] The concentration of the dispersant is generally between 0.1% and 1%, and the dispersion time should be long enough, usually 1 to 2 hours, to completely break up the agglomeration of the nanomaterials.

[0038] During ultrasonic dispersion, controlling the temperature at around 40°C can improve the dispersion effect. Too high a temperature can cause solvent evaporation or thermal decomposition of the nanomaterial. Use a thermometer to monitor the temperature of the dispersion to ensure that it remains within an appropriate range.

[0039] A method for preparing a lithium-sulfur battery separator comprises the following steps:

[0040] Ⅰ: Select materials;

[0041] II: Preparation of membrane materials;

[0042] III: functionalized diaphragm surface;

[0043] IV: Drying and heat treatment;

[0044] V: Testing and evaluation.

[0045] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lithium-sulfur battery separator, characterized in that: The following steps are involved: Step 1: Material preparation, using polyimide as the substrate, boron nitride as the two-dimensional material, and deionized water as the solvent; Step 2: Pretreatment of the substrate material: Place the substrate film on the sample stage of the plasma treatment equipment, close the equipment, evacuate to the set pressure, start the plasma treatment, set the power and time, and after the treatment is completed, take out the film and dry it naturally; Step 3: Preparation of dispersion: weigh 0.5g of boron nitride powder, add 0.1g of PVA to 100ml of deionized water, heat to 80°C and stir until completely dissolved to form a dispersant solution, add 0.5g of boron nitride powder to 100ml of dispersant solution, use an ultrasonic cleaner to ultrasonically disperse at 40°C for 2 hours to ensure that the boron nitride is evenly dispersed to form a stable boron nitride dispersion; Step 4: Preparation of the coating layer: using the immersion and pulling method, slowly immerse the pretreated polyimide film into the two-dimensional material dispersion, stay for 30 seconds, then pull it out of the liquid surface at a constant speed (1 mm / s), dry it naturally for 12 hours, repeat the above immersion and pulling process 2-3 times, and then carry out the next coating after each drying; Step 5: Curing treatment: put the coated film into an oven and heat it at 120°C for 1 hour to firmly fix the coating on the substrate, and then cool it naturally to room temperature to complete the preparation of the diaphragm; Step 6: Test optimization. Use a scanning electron microscope (SEM) to observe the surface morphology and coating uniformity of the diaphragm, measure the porosity through a porosimeter, and evaluate the wettability of the electrolyte using a contact angle meter. Apply the prepared diaphragm to lithium-sulfur batteries to test its cycle stability, rate performance, capacity retention and other indicators. According to the test results, adjust the dispersion content, coating times and other parameters to obtain the best diaphragm performance.

2. The method for preparing a lithium-sulfur battery separator according to claim 1, characterized in that: The substrate material pretreatment includes chemical modification and physical treatment. The chemical modification uses a modifier containing an amino group or a carboxyl group. The modifier (such as γ-aminopropyltriethoxysilane) is dissolved in an appropriate amount of solvent (such as ethanol) to prepare a solution with a concentration of 1%. The substrate film is immersed in the modifier solution to ensure that the film is completely immersed. The film is immersed at room temperature for 30 minutes, the film is taken out, rinsed with deionized water, excess modifier is removed, and the film is placed in an oven and dried at 80°C for 1 hour to firmly fix the modifier on the substrate surface.

3. The method for preparing a lithium-sulfur battery separator according to claim 2, characterized in that: The physical treatment uses a laser etching device, placing the substrate film on the workbench of the laser etching device, setting appropriate laser power and scanning speed, performing laser etching to form a uniform microstructure, cleaning with deionized water to remove the residues produced by etching, and placing the film in an oven to dry at 80°C for 1 hour.

4. The method for preparing a lithium-sulfur battery separator according to claim 1, characterized in that: The concentration of the dispersant is generally between 0.1% and 1%, and the dispersion time is ensured to be long enough, usually 1 to 2 hours, to completely break up the agglomeration of the nanomaterials.

5. The method for preparing a lithium-sulfur battery separator according to claim 1, characterized in that: During the ultrasonic dispersion, the temperature is controlled at about 40° C. to improve the dispersion effect. Too high a temperature may cause solvent evaporation or thermal decomposition of the nanomaterial. A thermometer is used to monitor the temperature of the dispersion to ensure that it remains within a suitable range.

6. The method for preparing a lithium-sulfur battery separator according to claim 1, characterized in that: The following steps are involved: Ⅰ: Select materials; II: Preparation of membrane materials; III: functionalized diaphragm surface; IV: Drying and heat treatment; V: Testing and evaluation.

Citation Information

Patent Citations

  • Functional composite membrane for lithium-sulfur battery and preparation method of functional composite membrane

    CN105140447A

  • Polymer film modified by fluororesin and preparation method thereof

    CN105175768A

  • Composite multi-arc-hole membrane material filled with boric nitride particles as well as preparation method and application thereof

    CN105206783A

Cited By

  • Nano-silica modified porous membrane, preparation method and application in zinc-bromine flow battery

    CN120300211A

  • Nano-silica modified porous membrane and preparation method and application in zinc-bromine flow battery

    CN120300211B

  • Preparation method of lithium-sulfur battery diaphragm

    CN121394762A